2017
DOI: 10.1016/j.applthermaleng.2016.11.179
|View full text |Cite
|
Sign up to set email alerts
|

Selection of wetted media for pre-cooling of air entering natural draft dry cooling towers

Abstract: HighlightsFour wetted media were comparatively studied for future pre-cooling design.Characteristics of wetted media suitable for pre-cooling were summarized.Media with middle efficiencies and pressure drops are superior for pre-cooling.Cellulose7060 is most promising for pre-cooling the 120m-high NDDCT. AbstractThe performance of natural draft dry cooling towers (NDDCTs) can be improved by wetted-medium evaporative pre-cooling. However, the pre-cooling benefit is season dependent and is significantly affected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(10 citation statements)
references
References 27 publications
0
9
0
1
Order By: Relevance
“…The stages [8] and layout [9] of the fill are optimized according to the airside velocity distribution to further improve the evaporated rate. There is about an average of 5% improvement of the heat transfer rate with water consumption of 25 kg/s [10,11]. However, during the weather with low temperature and/or high humidity, the loss of fills brings a decrease of the heat transfer rate [12].…”
Section: Introductionmentioning
confidence: 99%
“…The stages [8] and layout [9] of the fill are optimized according to the airside velocity distribution to further improve the evaporated rate. There is about an average of 5% improvement of the heat transfer rate with water consumption of 25 kg/s [10,11]. However, during the weather with low temperature and/or high humidity, the loss of fills brings a decrease of the heat transfer rate [12].…”
Section: Introductionmentioning
confidence: 99%
“…They pointed out that the dew point effectiveness ranged from 46.7% to 78.6% for the cooler with polystyrene and nylon fiber coated on the plate surface. He et al [18] developed a numerical model to study the evaporative pre-cooling performance of the cooling towers with two types wetted medium. It was reported that the Cellulose7060 allowed a marked improvement on the cooling efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…He et al investigated whether the precooling of inlet air using Munters media can enhance the performance of natural draft dry cooling tower (NDDCT) on hot and dry days. Three Munters media (CELdek7060, CELdek7090, and CELdek5090) of different thicknesses were used and it was found that precooling with 0.10 and 0.15 m CELdek7060 was best in performance among them.…”
Section: Introductionmentioning
confidence: 99%